EKSISTENSI SAKSI MAHKOTA KAITANNYA DENGAN SPLITSING DALAM PEMBUKTIAN PERKARA PIDANA - Ditapraja Adipatni, Sang Ayu; Sutarajaya, I Wayan; Bela Siki Layang, I Wayan (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
Crown witness is a testimony provided by a defendant used as a witness interchangeably or a defendant who becomes a witness for another defendant in the separate trial dockets (splitsing) where the crime is an inclusion offense. The existence of this crown witness is not strictly regulated in KUHAP, so that causing many juridical problems. On one side the existence of crown witness can be justified since the objective is to achieve sense of public justice. But in the other side the existence of crown witness is not justified because it contradicts with the rights and sense of justice of the defendant. Even the perception’s differences regarding crown witness also appear in a variety of jurisprudences of the Supreme Court’s decisions of Republic of Indonesia.
Keywords: splitsing, crown witness, evidence, criminal case